INFECÇÃO POR SARS-COV-2 EM PROFISSIONAIS DE SAÚDE EM HOSPITAIS TERCIÁRIOS DE CAMPO GRANDE - MS - Antonio Luiz Dal Bello Gasparoto (2022)
Studying the epidemiological, clinical and molecular aspects of SARS-CoV-2 infection and the identification of associated factors with infection in healthcare professionals can contribute to understanding the infection among this professionals. Considering the scarcity of data on the dynamics of infection by the new coronavirus in Brazil at the time, the present study aimed to 1) estimate the attack rate of SARS-CoV-2 infection in health professionals from two tertiary hospitals in Campo Grande, MS; 2) analyze demographic and clinical characteristics and risk factors; 3) identify circulating variants of the virus. A cohort, observational and prospective study was conducted with 554 health professionals from May 2020 to January 2021. During 12 visits, with an interval of 15 days, nasal and oropharyngeal secretion collections and a structured interview were performed. Detection of SARS-CoV-2 was performed by RT-qPCR and complete viral genome sequencing was performed on samples with the detectable virus. Most study participants were female (77.08%), white (57.40%), aged between 20 and 40 years (64.98%), predominantly overweight (37.90%), without comorbidities (74.72%). Most reported not using continuous medication (68.77%), having a scar from the BCG vaccine (91.69%), non-smokers and non-alcoholics (90.43%). Predominantly the participants were from the state referral hospital for Covid-19 (58.31%), had postgraduate degrees (54.33%), were part of the nursing staff (61.92%), were allocated in the Therapy Center Intensive Care (CTI) (37.36%) and reported having received two training sessions for the use and removal of PPE (79.43%). Active SARS-CoV-2 infection was confirmed in 28.51%, with 4.43% asymptomatic, 9.50% oligosymptomatic and 86.07% symptomatic. Monthly attack rates ranged from 0.51% to 9.52% and two peaks were identified in August and December 2020, with the highest attack rates at the referral hospital. The risk factors associated with a positive molecular diagnosis, regardless of the presence or absence of symptoms, were: being male, working at the referral hospital for Covid-19 and higher education. The symptoms associated with the positive diagnosis were: cough, myalgia, headache, anosmia and fever. The use of drugs or substances intended to prevent or treat the infection that were associated with active infection were hydroxychloroquine and zinc. The infection dynamics were similar between the health professionals studied and the population of Campo Grande city, both the first and second waves of Covid-19 . Among positive samples for SARS-CoV-2 RNA in the RT-qPCR technique, 35 (22.15%) were submitted to whole genome sequencing and five strains were detected, B.1.1.28, P .2, B.1.1.33 and N.4. Our results suggest that: 1) health professionals working in a reference hospital for Covid-19 had a higher incidence compared to the non-reference hospital; 2) the infection dynamics in the population studied followed the behavior of the infection in the general population in Campo Grande city; 3) asymptomatic infection in 4.43% and oligosymptomatic in 9.50%, could go unnoticed by the routine screening of symptomatic patients in occupational health services; 4) the distribution of circulating SARS-CoV-2 strains among the health professionals under study coincided with the dominant strains in Brazil.